2019
DOI: 10.1371/journal.ppat.1007650
|View full text |Cite
|
Sign up to set email alerts
|

Varicella zoster virus productively infects human peripheral blood mononuclear cells to modulate expression of immunoinhibitory proteins and blocking PD-L1 enhances virus-specific CD8+ T cell effector function

Abstract: Varicella zoster virus (VZV) is a lymphotropic alpha-herpesvirinae subfamily member that produces varicella on primary infection and causes zoster, vascular disease and vision loss upon reactivation from latency. VZV-infected peripheral blood mononuclear cells (PBMCs) disseminate virus to distal organs to produce clinical disease. To assess immune evasion strategies elicited by VZV that may contribute to dissemination of infection, human PBMCs and VZV-specific CD8+ T cells (V-CD8+) were mock- or VZV-infected a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 48 publications
2
35
0
Order By: Relevance
“…The capacity of VZV to productively infect and modulate the function of monocytes may enhance the ability of VZV to establish an infection in the host. This work was corroborated by a report demonstrating VZV infection of monocytes, NKT cells and B lymphocytes (150) and by productive infection of a THP-1 monocytic cell line (89). Although evidence suggesting monocyte differentiation to macrophage may be influenced by VZV infection in vivo, macrophage infection in vitro has previously been observed (56,148).…”
Section: Vzv Infection and Manipulation Of Monocytes And Macrophagessupporting
confidence: 75%
See 3 more Smart Citations
“…The capacity of VZV to productively infect and modulate the function of monocytes may enhance the ability of VZV to establish an infection in the host. This work was corroborated by a report demonstrating VZV infection of monocytes, NKT cells and B lymphocytes (150) and by productive infection of a THP-1 monocytic cell line (89). Although evidence suggesting monocyte differentiation to macrophage may be influenced by VZV infection in vivo, macrophage infection in vitro has previously been observed (56,148).…”
Section: Vzv Infection and Manipulation Of Monocytes And Macrophagessupporting
confidence: 75%
“…Moreover, VZV infected NK cells are capable of transmitting infection to epithelial or fibroblast cells in culture and can upregulate skin-homing chemokine receptors, suggesting a potential role in viral dissemination during pathogenesis (114). Jones and co-workers in a later study also demonstrated VZV infection of PBMC derived NK cells (150). A case report of severe, persistent varicella identified VZV DNA in NK cells, amongst other lymphocyte populations (161), however targeted investigation of NK cell infection in additional varicella patients is needed to corroborate the in vitro findings.…”
Section: Importance Of Nk Cells In the Control Of Vzv Infectionmentioning
confidence: 95%
See 2 more Smart Citations
“…In addition, T cells infected by the closest relative to VZV, simian varicella virus, have been found in the ganglia of primates during primary infection (32). More recently, other immune cells (monocytes, NK cells, NKT cells, and B cells, in addition to both CD4 + and CD8 + T cells) have been shown to support productive infection of VZV (33, 34) and could potentially migrate and transfer the virus to sensory neurons. Such routes of infection would presumably enable direct access of the virus to the neuronal cell body.…”
Section: Discussionmentioning
confidence: 99%